Family life of the Haidas, Queen Charlotte Islands [electronic resource] - Harrison, C. (Charles), Rev. ([S.l. : s.n., 1892)
From: Journal of the Royal Anthropological Institute. Caption title. Electronic reproduction. Mode of access: Internet. 44